Management of Cough - Arief Bakhtiar; Putri Mega Juwita (Jurnal Respirasi, 2020)
Cough is the most frequent symptom for which patients consult with their health care provider throughout the world. This symptom could be happened not only in sick individuals but also healthy individuals. At some stage, it is distressing, inhibits normal social activities, and reduces quality of life. Besides these detrimental effects, cough is the most effective defense mechanism to eliminate foreign materials, including various pathogens, from the respiratory tract. It begins with a series of breathing maneuvers which triggers sudden expulsion of air which is divided into three phases, i.e. inspiration, compression, and expiration phase. Cough occurs due to activation of mechanical or chemical sensory receptors in the larynx and lower respiratory tract which stimulates reflex arc complex. This stimulus is then transmitted to the afferent pathway to the cough center in the medulla through the vagus nerve to trigger expiration muscles to produce cough. It is important to know the cause of cough because cough is an indicator for patients and doctors for early diagnosis and therapy of disease. Therefore, cough is classified into acute, subacute, and chronic according to its duration. Available medications for symptomatic management of cough are inadequate due to lack of proven efficacy and/or their undesirable or intolerable side effects. This article aims to provide information on cough management to improve therapeutic effectiveness and patient quality of life.